Use of temporal immersion systems for the in vitro multiplication of Anthurium andraeanum Lind. var. Lambada shoots - Nydia del Rivero Bautista; Elisa Quiala; Daniel Agramante; Raúl Barbón; Wilder Camacho; Lester Morejón; Marta Pérez (Biotecnología Vegetal, 2004)
Two methods to improve the efficiency in the multiplication of shoots of Anthurium andraeanum Lind., they were used to optimize the frequencies of immersion of the explants using a System of Temporary Immersion. The relative efficiency of the method conventional means of culture semisolid for the multiplication of shoots was compared with the method of System of Temporary Immersion. The highest rate of multiplication of shoots was reached using six immersions four times a day during two minutes, controlling the immersion cycles achieves plants better developed and bigger multiplication coefficient. The plantlets multiplied through this method were harvested with 2 to 3 cm of longitude containing from two to five leaves after a period of culture of 50 days. The formation of callus, hiperhidricity and other abnormalities were not observed during the process. The plants obtained by this method were taken to rooting in medium of culture semisólid. This system avoids risks of contamination, it increases yields, it reduces manpower costs and of containers. This technique for its relationship benefit-cost has significant implications for the commercial propagation of the Anthurium.